Culture and Arts Activities add excitement to UMP Convocation Expo - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) organised a culture and arts event, ‘Santai Seni Warisan’, that simply add to the fun of the Convocation Expo that was held in conjunction with the university’s 13th Convocation Ceremony scheduled on November 10 and 11 at its Gambang Campus Sports Complex.